(untitled) (Fiep Bulletin - online, 2011)
The Climacteric is a transition from the reproductive to the non-reproductive marked by changes that involve the body of the woman. Gynecologic therapy has options for prevention and treatment of changes caused in the climacteric. The aim of this study was to evaluate the influence of Kegel exercises in the loss of function of the perineal muscles of the pelvic floor in menopausal women. We evaluated 20 women aged 40 to 76 years, divided into two groups: Group I: physically active and Group II: non-practicing physical activity. Both groups filled out a questionnaire Female Sexual Quotient (SQ-F) related to female sexual function and performed perineal exercises contractions. Each participant received a table to organize the number of contractions performed weekly on a total of 4 weeks. It was observed that most women reduces the frequency of sex after menopause. Physical activity did not interfere in the improvement of perineal function. Physiological response were more on women who did not exercise. It was found that the Kegel exercises and physical exercise on the physiological perineal muscle.